Functional MRI Shows Altered Deactivation and a Corresponding Decrease in Functional Connectivity of the Default Mode Network in Patients with Gliomas - Maniar, Y.M.; Peck, K.K.; Jenabi, M.; Gene, M.; Holodny, A.I. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: The default mode network normally decreases in activity during externally directed tasks. Although default mode network connectivity is disrupted in numerous brain pathologies, default mode network deactivation has not been studied in patients with brain tumors. We investigated default mode network deactivation with language task–based fMRI by measuring the anticorrelation of a critical default mode network node, the posterior cingulate cortex, in patients with gliomas and controls; furthermore, we examined default mode network functional connectivity in these patients with task-based and resting-state fMRI.MATERIALS AND METHODS: In 10 healthy controls and 30 patients with gliomas, the posterior cingulate cortex was identified on task-based fMRI and was used as an ROI to create connectivity maps from task-based and resting-state fMRI data. We compared the average correlation in each default mode network region between patients and controls for each correlation map and stratified patients by tumor location, hemisphere, and grade.RESULTS: Patients with gliomas (P = .001) and, in particular, patients with tumors near the posterior default mode network (P < .001) showed less posterior cingulate cortex anticorrelation in task-based fMRI than controls. Patients with both left- and right-hemisphere tumors, as well as those with grade IV tumors, showed significantly lower posterior cingulate cortex anticorrelation than controls (P = .02, .03, and <.001, respectively). Functional connectivity in each default mode network region was not significantly different between task-based and resting-state maps.CONCLUSIONS: Task-based fMRI showed impaired deactivation of the default mode network in patients with gliomas. The functional connectivity of the default mode network in both task-based and resting-state fMRI in patients with gliomas using the posterior cingulate cortex identified in task-based fMRI as an ROI for seed-based correlation analysis has strong overlap.BOLDblood oxygen level–dependentDMNdefault mode networkFCfunctional connectivityIPLinferior parietal lobuleLIPLleft inferior parietal lobulemPFCmedial prefrontal cortexPCCposterior cingulate cortexRIPLright inferior parietal lobulers-fMRIresting-state fMRItb-fMRItask-based fMRI